El diseño de una guía gastronómica de platos culinarios, reflejados en el diseño web, como estrategia para la difusión de la identidad y cultura del cantón Pelileo. - Quiroz Chacón, Susanne Estefania (2023)
The purpose of this research was to design a gastronomic guide of culinary dishes that represent the Pelileo canton, using web design as a strategy to disseminate the identity and culture of Pelileo, where the gastronomy of the Pelileo canton reflects its unique cultural heritage that by its combination of indigenous and mestizo customs has produced delicious and diverse dishes that represent the local identity. However, due to a lack of visibility and proper promotion, many of these culinary treasures are at risk of being lost over time. Therefore, under the research line of the study of art, culture, gastronomy and its tourist environment, through the design applied to historical-cultural research and management, the main objective of this research is to design a gastronomic guide of traditional dishes, reflected in the web design for the dissemination of the cultural identity of the Pelileo canton, allowing website visitors to know the dishes, their ingredients, preparation and their cultural context, however, by using web design effectively, this guide gastronomy aims to promote pride and appreciation of the identity and culinary culture of the Pelileo canton. The development of the project covered the origin, changes and contributions through the history of the main ingredients that make up the traditional menu of the city as well as the identity that they bring to the town. The methodology of this research project was the user centered design, where the needs and preferences of the target audience are understood, conducting surveys, focus groups with visitors, local residents and cooking experts, high satisfaction was obtained about the importance of Traditional gastronomy as a cultural identity of the Pelileo canton, however, currently they consider that Fritada and Tamales are the main dishes of the place, not to mention the following dishes that are equally relevant such as roast guinea pig, pot empanadas, the caucara, the hornado and the black pudding. The web design of the guide was concluded in an attractive and functional way, which was adapted to different media to provide a fluid and accessible user experience. To attract visitors, visual media such as high-quality images of Pelileo's iconic dishes and places will be used, also the easy-to-navigate website, was determined with clear categories for the different types of dishes and sections dedicated to the history and culinary culture of the canton. In conclusion, the dissemination of this rich culinary heritage not only helped local tourism, but also contributed to local culture, where the web guide served as a useful tool to disseminate Pelileo's culinary legacy at the cantonal level.